Coaching winning sales teams insights from the world of sport and business - Chapman, Tim; Pickford, Lynn; Smith, Anthony A. 1959- (Emerald publishing, 2020)
CONTENTS: 1. Introduction 2. You as Coach, Your Inner Coach 3. The Outer Coach: The Skills and Behaviours of Great Coaches 4. Being Coached 5. Structure, Process and Models 6. Preparing to Coach 7. Coaching Winning Sales Teams in Action 8. Coaching Winning Sales Teams, The How 9. Final Thoughts 10. Meet Our Coaches
Keywords: Sales personnel -- Training of; Employees -- Coaching of; Personal coaching; Verkäufer; Vertrieb; Coaching